The Impact of Gluten Friendly Flour on the Functionality of an Active Drink: Viability of Lactobacillus acidophilus in a Fermented Milk - Speranza, Barbara; Bevilacqua, Antonio; Campaniello, Daniela; Sinigaglia, Milena; Musaico, Daniela; Corbo, Maria R.; Lamacchia, Carmela (Frontiers in Microbiology, 2018)
The Gluten Friendly™ Technology is an innovative method that induces structural changes in gluten proteins. In this paper a synbiotic fermented milk, containing Lactobacillus acidophilus La-5 and Gluten Friendly Flour (GFF), was proposed. A mixture design was used to combine flour, temperature and probiotic to study the effects of these variables on the acidification. The experiments were done on both GFF and control flour (CF). Thus, the following conditions were chosen to produce the fermented milk: L. acidophilus at 6.5 log cfu/ml; flour at 2.5 g/l; temperature at 37°C. Then, the fermented milk was produced and stored at 4°C for 90 days. The most important result was the positive effect of GFF on the viability of the probiotic, with a prolongation of the shoulder length to 20 days (12-13 days in the control). Moreover, GFF did not act on the sensory scores and on the physico-chemical parameters.